PENGARUH DANA PIHAK KETIGA (DPK) TERHADAP PENYALURAN KREDIT MODAL KERJA PADA PT. BANK MANDIRI (PERSERO), TBK, KANTOR WILAYAH X MAKASSAR - Musliha Shaleh (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
The purpose of this study is to determine the amount of influence of third party funds on the distribution of working capital loans at PT. Bank Mandiri (Persero), Tbk, Regional Office X Makassar. The method used in this research is multiple linear regression analysis and correlation analysis. The results of this study are Based on the results of data analysis above, it can be concluded that the Third Party Fund (DPK) significant effect on the Distribution of Working Capital Credit at PT. Bank Mandiri (Persero), Tbk, Regional Office X Makassar